D-Dimers and MPO Are No Suitable Biomarkers for Application in Abdominal Aortic Aneurysm (AAA) Surveillance in a Real-World Setting of Vascular Surgery Patients - Hans Siegrist; Anja Spieler; Andreas S. Peters; Karola H. Passek; Dittmar Böckler; Susanne Dihlmann (Biomolecules, 2024)
There is currently no clinically valid biomarker for predicting the growth and prognosis of abdominal aortic aneurysms (AAA). The most promising candidates with the highest diagnostic values are plasma D-dimers and markers of activated neutrophils, i.e., myeloperoxidase (MPO) or cell-free DNA. So far, case-control studies on these markers have been performed almost exclusively using healthy individuals as controls. To validate the value of these markers in the clinical setting of a vascular surgery department, we analysed the diagnostic and prognostic potential of plasma D-dimers and MPO in 177 AAA patients versus 138 non-AAA patients with different vascular diseases. Significantly elevated levels of D-dimers were recorded for AAA patients compared with non-AAA patients, although the difference between the two groups was significantly smaller than that in other studies comparing AAA patients with healthy controls. Surprisingly, MPO levels were significantly higher in non-AAA patients than in those with AAA. After adjusting for the confounding factors of sex, peripheral artery disease (PAD) and internal carotid stenosis in multivariate regression models, neither D-dimers nor MPO remained independent correlates of AAA. In contrast, D-dimer plasma levels correlated well with the maximal aortic diameter. Combined analysis of D-dimers and circulating cell-free DNA levels derived from a previous study failed to improve the predictive values for the maximal aortic diameter. In conclusion, our data show that D-dimers and MPO are not suitable biomarkers for monitoring AAA in a real-world setting of mixed vascular surgery patients.